Synthesis and applications of aminated biopolymers - Phillips, Thaakirah (Department of Chemistry, 2025)
Cellulose and chitin have a significant role in the biorefinery where biomass is converted into value-added products. Native cellulose and chitin are known to be insoluble in most common organic and aqueous solvents and are therefore physically and chemically modified with different functionalities to improve solubility to enable further application and modulate bioactivity. The introduction of amino groups into biopolymers is one method to improve solubility in water and enhance other properties such as bioactivity. The solubility of polymers in water is advantageous and enables opportunities for applications in many industries. A simple, green and sustainable synthetic method was sought as an improvement to prior methods using hazardous reagents and producing immense amounts of waste. Innovative synthetic methods were developed for the synthesis of amino- and diamino celluloses. A sustainable, economically viable process for biopolymer amination was sought via substitution of C-6 tosyl esters or via reductive amination of biopolymer aldehyde derivatives. To this end, C-6 amino cellulose was synthesised by a novel synthetic pathway in which cellulose is firstly tosylated using a surfactant-mediated solvent system to yield DMSO-soluble cellulose tosylates. Subsequently the C-6 partially tosylated cellulose was subjected to a Swern-like oxidation to yield the required C-6 aldehyde functionality primed for reductive amination. The same oxidation-reductive amination strategy was attempted on chitin or chitosan. The established periodate oxidation of cellulose provided dialdehyde cellulose (DAC) ready for reductive amination. The synthesised diamino and amino celluloses were DMSO-soluble and were tested for cytotoxicity against brain cancer cell lines. Cytotoxicity studies showed that the aminated celluloses did not display any inherent anticancer activity, however, it would be suitable for drug conjugation and delivery. Previous studies have showed the successful use of recyclable 6-deoxy-6-amino chitosan as an aqueous-soluble solid support for platinum group metal catalysts. This motivated the use of an amination strategy for the immobilisation of pyridoxal and pyridoxal 5'-phosphate (PLP) for application in non-enzymatic deamination of L-phenylalanine to phenylpyruvate. An ionic complex between PLP and Q188 was formed and successfully utilised to convert L- phenylalanine into phenylpyruvate, however, the polymer complex showed a decline in activity over time possibly due to the leaching of PLP. Therefore, immobilisation of PLP via covalent bonding was explored, however, the pyridoxal immobilised biopolymers synthesised were insoluble in water and could not be used in simulating non-enzymatic deamination reactions.